2016
DOI: 10.1016/j.semcdb.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Planar cell polarity (PCP) proteins and spermatogenesis

Abstract: In adult mammalian testes, spermatogenesis is composed of several discrete cellular events that work in tandem to support the transformation and differentiation of diploid spermatogonia to haploid spermatids during the seminiferous epithelial cycle. These include: self-renewal of spermatogonial stem cells via mitosis and their transformation into differentiated spermatogonia, meiosis I/II, spermiogenesis and the release of sperms at spermiation. Studies have shown that these cellular events are under precise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 125 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…However, our results provide evidence indicating that boars with the homologous AA genotype at rs345056502 (EML5 gene) were more susceptible to post-thaw acrosome damage and LPO, while the homologous TT genotype of the PRICKLE1 gene contributed to greater cryo-induced DNA damage. Moreover, microtubule-associated proteins (MAPs) in sperm cells have various functions including modulation of actin cytoskeletal function during spermatogenesis [49]. Collectively, EML5 and PRICKLE1 are implicated in microtubule (MT) dynamics in the testis, and mutations in their genotypes could affect the physiological and structural function of the sperm following cryopreservation.…”
Section: Snp Associations With Post-thaw Semen Qualitymentioning
confidence: 99%
“…However, our results provide evidence indicating that boars with the homologous AA genotype at rs345056502 (EML5 gene) were more susceptible to post-thaw acrosome damage and LPO, while the homologous TT genotype of the PRICKLE1 gene contributed to greater cryo-induced DNA damage. Moreover, microtubule-associated proteins (MAPs) in sperm cells have various functions including modulation of actin cytoskeletal function during spermatogenesis [49]. Collectively, EML5 and PRICKLE1 are implicated in microtubule (MT) dynamics in the testis, and mutations in their genotypes could affect the physiological and structural function of the sperm following cryopreservation.…”
Section: Snp Associations With Post-thaw Semen Qualitymentioning
confidence: 99%
“…For instance, the release of sperm takes place at stage VIII of the cycle, coinciding with the appearance of step 8 spermatids and the preleptotene spermatocytes in the seminiferous epithelium. PCP refers to the orderly alignment of a field of polarized cells within the plane of an epithelium such as those found in wing cell hair in Drosophila and cell hair of the inner ear in mammals 15 , 23 , 32 . Using confocal microscopy, developing spermatids in particular step 17–19 spermatids in stage V–VIII tubules were found to display PCP in the reconstructed 3D image such as the one shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported elongating/elongated spermatids also displayed PCP in adult rat testes in which the proximal end of polarized spermatid heads were aligned uniformly across the plane of the seminiferous epithelium by confocal microscopy and 3-dimensional (D) reconstruction of the seminiferous tubules 28 . Studies also have identified several PCP genes/proteins in the mammalian testis 29 32 . Among these, Vangl2 was found to regulate the apical ES at the spermatid-Sertoli cell interface and at the Sertoli cell–cell interface at the blood-testis barrier (BTB) called basal ES 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Planar polarity has been reported from as early as epiblast formation in zebrafish [ 5 ] and primitive endoderm formation in mouse [ 6 ]. Its loss is implicated in neural tube closure defects [ 7 ], spermatogenesis defects [ 8 ], deafness [ 9 ], and heart defects [ 10 ]. As such the underlying mechanisms are of broad interest.…”
Section: Introductionmentioning
confidence: 99%